Biased anti-idiotype response in rabbits leads to high-affinity monoclonal antibodies to biologics - Christina Großerichter-Wagener; Dorien Kos; Astrid van Leeuwen; Lisanne Dijk; Jorn Jeremiasse; Floris C. Loeff; Theo Rispens (mAbs, 2020)
Antibody formation to human(ized) therapeutic antibodies in humans is highly skewed toward anti-idiotype responses, probably because the idiotype is the only ‘foreign’ part of the antibody molecule. Here, we analyzed antibody responses to F(ab’)2 fragments of a panel of 17 human(ized) therapeutic antibodies in rabbits. Homology between the rabbit germline and the human(ized) antibodies is moderate not only for the variable domains (both the complementarity-determining regions and the framework regions), but also for the constant domains (66% or less). Nevertheless, we observed a highly skewed anti-idiotype response in all cases, with up to >90% of the antibodies directed toward the idiotype. These results indicate that the idiotype may be inherently immunodominant. We used these biased responses to raise monoclonal rabbit anti-idiotype antibodies against secukinumab, ustekinumab, reslizumab, mepolizumab, palivizumab, and dupilumab and demonstrate the potential to develop sensitive pharmacokinetic assays with these antibodies.